2023
DOI: 10.1101/2023.10.25.23297469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peripheral Transcriptomics in Acute and Long-Term Kidney Dysfunction in SARS-CoV2 Infection

Pushkala Jayaraman,
Madhumitha Rajagopal,
Ishan Paranjpe
et al.

Abstract: Background. Acute kidney injury (AKI) is common in hospitalized patients with SARS-CoV2 infection despite vaccination and leads to long-term kidney dysfunction. However, peripheral blood molecular signatures in AKI from COVID-19 and their association with long-term kidney dysfunction are yet unexplored. Methods. In patients hospitalized with SARS-CoV2, we performed bulk RNA sequencing using peripheral blood mononuclear cells (PBMCs). We applied linear models accounting for technical and biological variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…The eGFR of the severe acute COVID-19 cohort in our dataset was found to be significantly lower than that of the mild cohort ( Figure S8 ). Since it was recently reported that AKI in severe COVID-19 shared mechanistic similarities with sepsis-associated AKI 45, 46 , we sought to look at the mechanistic similarities between the severe COVID-19 and the non-COVID AKI urinary proteome. While the separation between non-COVID AKI and COVID-19 samples was not extensive, we observed a clear distinction between disease and healthy samples ( Figure S9A ).…”
Section: Resultsmentioning
confidence: 99%
“…The eGFR of the severe acute COVID-19 cohort in our dataset was found to be significantly lower than that of the mild cohort ( Figure S8 ). Since it was recently reported that AKI in severe COVID-19 shared mechanistic similarities with sepsis-associated AKI 45, 46 , we sought to look at the mechanistic similarities between the severe COVID-19 and the non-COVID AKI urinary proteome. While the separation between non-COVID AKI and COVID-19 samples was not extensive, we observed a clear distinction between disease and healthy samples ( Figure S9A ).…”
Section: Resultsmentioning
confidence: 99%